Jesus and the land : the New Testament challenge to "Holy Land" theology - Burge, Gary M., 1952- (Grand Rapids, Mich. : Baker Academic, 2010)
This accessible volume describes first-century Jewish and Christian beliefs about the land of Israel and offers a full survey of New Testament passages that directly address the question of land and faith. Respected New Testament scholar Gary M. Burge examines present-day tensions surrounding "territorial religion" in the modern Middle East, helping contemporary Christians develop a Christian theology of the land and assess Bible-based claims in discussions of the Israeli-Palestinian struggle.
The biblical heritage : the Old Testament -- The covenant and the land -- The possession and loss of land -- After the exile -- The rabbis: reinforcing commitments -- Diaspora Judaism and the land : The Jewish Diaspora and the land -- Fidelity and separation -- The land redefined -- Jesus and the land : land and politics in Jesus' world -- Continuity and discontinuity -- Critical passages in the Gospels -- The fourth Gospel and the land : land, geography, and theology -- The land and messianic fulfillment -- Jesus and holy space -- The book of Acts and the land : rethinking restoration -- Stephen : a theology for the world -- Paul : a missionary for the world -- Syrian Antioch : a world-class city -- Paul and the promises to Abraham : initial observations -- Abraham in early Judaism -- Abraham in Galatians 3-4 -- Abraham in Romans 4 -- The paradox in Romans 9-11 -- Paul and the temple -- Developments beyond Paul : the book of Hebrews -- Revelation -- Land, theology, and the church : a conversation in Jerusalem -- Christian Zionist territorial theology -- Building a Christian territorial theology? -- Thinking Christianly about the land.
Includes bibliographical references (p. 132-145) and index.
Keywords: Land tenure -- Religious aspects -- Christianity; Land tenure -- Biblical teaching; Land tenure -- Middle East; Distributive justice -- Religious aspects; Bible -- Geography; Bible -- Criticism, interpretation, etc; christianisme -- x